1996
DOI: 10.1183/09031936.96.09040669
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between radiological pattern and cell-mediated immune response in Mycoplasma pneumoniae pneumonia

Abstract: The aim of this study was to determine the relationship between the radiological pattern of Mycoplasma pneumoniae and the level of cell-mediated immunity of the host.Computed tomographic (CT) scans of the chest and the results of the purified protein derivative (PPD) test were studied during the acute stage of infection in 54 patients with M. pneumoniae pneumonia. The CT findings were used to divide the patients into two groups: one group had a predominance of nodular opacities with a centrilobular distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Current evidence from human and animal studies suggests that cytokine production and lymphocyte activation may either minimize disease through the enhancement of host defense mechanisms or exacerbate disease through immunological lesion development. Thus, the more vigorous the cell-mediated immune response and cytokine stimulation, the more severe the clinical illness and pulmonary injury (78,201,305,338,342,(404)(405)(406). This concept of immune-mediated lung disease provides a basis for consideration of immunomodulatory therapeutics in addition to conventional antimicrobial therapies in management of disease due to M. pneumoniae.…”
Section: Cytotoxicity and Inflammationmentioning
confidence: 99%
“…Current evidence from human and animal studies suggests that cytokine production and lymphocyte activation may either minimize disease through the enhancement of host defense mechanisms or exacerbate disease through immunological lesion development. Thus, the more vigorous the cell-mediated immune response and cytokine stimulation, the more severe the clinical illness and pulmonary injury (78,201,305,338,342,(404)(405)(406). This concept of immune-mediated lung disease provides a basis for consideration of immunomodulatory therapeutics in addition to conventional antimicrobial therapies in management of disease due to M. pneumoniae.…”
Section: Cytotoxicity and Inflammationmentioning
confidence: 99%
“…16 Tuberculin skin test reactivity can also act as a risk marker for Mycoplasma pneumonia among the elderly 17 and is correlated with clinical severity and radiographic presentation of pulmonary lesions caused by M pneumonia. 18 Beyond this evidence, the literature on BCG-ALRI associations remain limited, likely due to several factors including historical difficulties in ascertaining vaccination status from health records or vaccination cards, [19][20][21] high BCG vaccination rates in the general population (85% worldwide coverage rate with national coverage ranging from 43% to 99%), 1 and ethical constraints in conducting randomized clinical trials to evaluate routinely used childhood vaccines. 22,23 Further complicating this line of research has been the established ineffectiveness of BCG for inducing protective immunity against tuberculosis among adults and its contraindicated use among HIV-infected individuals.…”
mentioning
confidence: 99%
“…One point which seems to be sure is that pneumonia, the hallmark of M. pneumoniae infection, is a consequence of a host immune response, particularly of cellular immunity (2,4,6). In this respect, previous studies have suggested that a T-helper 1 (Th1)-type response of the host may play an important role in developing pathologic features as well as in radiographical patterns of M. pneumoniae pneumonia (34,35). At the same time, it has been reported that a local immune response on the pulmonary surface of the host may play an important role in developing extrapulmonary diseases associated with M. pneumoniae (23; M. Narita, Letter, Clin.…”
mentioning
confidence: 99%